Vaginal microbiome in early pregnancy and subsequent risk of spontaneous preterm birth: a case–control study. (27th June 2018) - Tabatabaei, N; Eren, AM; Barreiro, LB; Yotova, V; Dumaine, A; Allard, C; Fraser, WD
Abstract : Objectives: To explore differences in the vaginal microbiome between preterm and term deliveries. Design: Nested case–control study in 3D cohort (design, develop, discover). Setting: Quebec, Canada. Sample: Ninety‐four women with spontaneous preterm birth as cases [17 early (<34 weeks) and 77 late (34–36 weeks) preterm birth] and 356 women as controls with term delivery (≥37 weeks). Methods: To assess the vaginal microbiome by sequencing the V4 region of the 16S ribosomal RNA (rRNA) gene in swabs self‐collected during early pregnancy. Main outcome measures: Comparison of relative abundance of bacterial operational taxonomic units and oligotypes and identifying vaginal community state types (CSTs) in early or late spontaneous preterm and term deliveries. Results: Lactobacillus gasseri/ Lactobacillus johnsonii (coefficient −5.36, 95% CI −8.07 to −2.65), Lactobacillus crispatus (99%)/ Lactobacillus acidophilus (99%) (−4.58, 95% CI −6.20 to −2.96), Lactobacillus iners (99%)/ Ralstonia solanacearum (99%) (−3.98, 95% CI −6.48 to −1.47) and Bifidobacterium longum / Bifidobacterium breve (−8.84, 95% CI −12.96 to −4.73) were associated with decreased risk of early but not late preterm birth. Six vaginal CSTs were identified: four dominated by Lactobacillus ; one with presence of bacterial vaginosis‐associated bacteria ( Gardnerella vaginalis, Atopobium vaginae and Veillonellaceae bacterium) (CST IV); and one with nondominance of Lactobacillus (CST VI). CST IV was associated with increased risk of early (4.22, 95% CI 1.24–24.85) but not late (1.63, 95% CI 0.68–5.04) preterm birth, compared with CST VI. Conclusions: Lactobacillus gasseri / L. johnsonii, L. crispatus / L. acidophilus, L. iners / R. solanacearum and B. longum / B. breve may be associated with decreased risk of early preterm birth. A bacterial vaginosis‐related vaginal CST versus a CST nondominated by Lactobacillus may be associated with increased risk of early preterm birth. Tweetable abstract: Largest study of its kind finds certain species of vaginal Lactobacillus + Bifidobacterium may relate to lower risk of preterm birth. Tweetable abstract: Largest study of its kind finds certain species of vaginal Lactobacillus + Bifidobacterium may relate to lower risk of preterm birth.